Sustainable Infrastructure Development in The IKN Region (Nusantara Capital): Simulation of The Smart Self-Sustaining Urban Center Area Development - Laksono, Naufal Budi; Latief, Yusuf (UI Scholars Hub, 2024)
Embarking on the quest for a sustainable urban future, this research immerses itself in the vibrant landscape of